A leitura crítica em língua estrangeira (Cadernos de Linguagem e Sociedade, 2010)
The purpose of this study is to verify whether non-native speakers of English in an advanced level of linguistic competence are able to perform the kind of critical reading described by Norman Fairclough in Language and Power as specifically oriented towards the identification of ideological assumptions embedded in several types of discourse.